C++ cheng xu she ji yuan li yu shi jian.Jin jie pian : (yuan shu di 2 ban) - Stroustrup, Bjarne (Pearson, 2021)
Detailed summary in vernacular field.
Includes bibliographical references
Keywords: C++ (Computer program language); C++ (Langage de programmation)